PERAN KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN PELANGGAN DI WARUNG BAJAK LAUT KEDIRI - Laksonowati , Diani Puji (Universitas Nusantara PGRI Kediri, 2022)
This look at targets to decide the role of interpersonal verbal exchange in increasing customer pride. customer pride is the dependent variable on this have a look at, whilst the impartial variable is interpersonal communique. The records become obtained from the Kediri Pirate shop clients. The populace in this have a look at have been all clients of the Kediri Pirate store. The number of samples on this have a look at were eighty two respondents. The research technique used is a easy linear regression evaluation technique with a 5% self assurance stage to obtain a complete photo of the connection among one variable and any other. The effects of the partial take a look at display that zero.000 <0.05 and tcount value of 1.989 while ttable is 9.467 which means tcount > ttable so that it method H0 is rejected and H1 is common. Interpersonal communique variables partially have a great effect on patron pleasure.